The increase of firearm-related violence in Sweden - Khoshnood, Ardavan (Forensic Sci Res, 2017)
Firearm-related violence is common in our contemporary world and causes serious harm to humans as well as to the society. One of the countries in which firearm-related violence is increasing is Sweden and its most southern region, Skane, in which Malmo, Sweden's third largest city, is highly affected. If not contained and limited, Sweden risks becoming more and more violent.